Efficiency at Maximum Power of Endoreversible Quantum Otto Engine with Partial Thermalization in 3D Harmonic Potential - Zettira, Zahara; Sutantyo, Trengginas Eka Putra; Abdullah, Zulfi (Jurusan Fisika FMIPA Universitas Andalas, 2024)
We study the partial thermalization to the effect of efficiency at maximum power (EMP) of a quantum Otto engine using Bose-Einstein Condensation in 3D harmonic potential. Partial thermalization occurs at a finite-time isochoric process, preventing the medium from achieving equilibrium with reservoirs, leaving it in a state of residual coherence. Under these circumstances, the performance of the engine can be seen from its power and EMP. The 3D harmonic potential is used to generate an excitation of energy during the expansion and compression. The total energy is defined by the total work done in a cycle. Using Fourier’s law in conduction, we found that power explicitly depends on the duration of heating and cooling stroke time and efficiency of the engine; that is the higher stroke time and efficiency, the less power output. In order to find EMP, we maximize power with respect to compression ratio κ, and we found that EMP also depends on the isochoric heating and cooling process. By varying the stroke time of the isochoric process, EMP slightly decreases with increasing isochoric time due to entropy production. However, adjusting cooling stroke time more extended than heating stroke time could significantly improve the EMP of Otto Engine.